Genetic Aspects of Problematic and Risky Internet Use in Young Men—Analysis of ANKK1, DRD2 and NTRK3 Gene Polymorphism - Rył, Aleksandra; Tomska, Natalia; Jakubowska, Anna; Ogrodniczak, Alicja; Palma, Joanna; Rotter, Iwona (Genes, 2024)
Background: Internet addiction disorder (IAD) is characterized by an excess of uncontrolled preoccupations, urges, or behaviors related to computer use and Internet access that culminate in negative outcomes or individual distress. PIU includes excessive online activities (such as video gaming, social media use, streaming, pornography viewing, and shopping). The aim of this study was to analyze the association of gene polymorphisms that may influence the severity of risky behaviors in young men with the frequency of Internet use. We speculate that there are individual differences in the mechanisms of Internet addiction and that gene–hormone associations may represent useful biomarkers for subgroups of individuals. Materials and Methods: The study was conducted in a sample of 407 adult males. Subjects were asked to complete the Problematic Internet Use Test (PIUT). Serum was analyzed to determine concentrations of luteinizing hormone (LH), follicle stimulating hormone (FSH), testosterone (TT), sex hormone binding protein (SHBG), dehydroepiandrosterone sulfate (DHEA-S), estradiol (E2), prolactin (PRL), insulin (I), serotonin (5-HT), and dopamine (DA), as well as DRD2, ANKK1, and NTRK3 gene polymorphisms. Results: In the analysis of the ANKK1 gene, there was a specific association between ANKK1 polymorphisms and PRL and 5-HT blood concentrations. There was also an association between the ANKK1 polymorphisms and LH and DA concentrations. When analyzing the DRD2 gene polymorphism, we found that in the group with a moderate level of Internet dependence, there was an association between both the G/GG and GG/GG polymorphisms and FSH concentration. Conclusions: Our study found that there may be an association between the NTRK3 gene polymorphism and PIU. The polymorphisms of ANKK1 and DRD2 genes may be factors that influence the concentrations of hormones (PRL, 5-HT, DA) that are associated with the results obtained in PIU.